OPTIMASI PERAKITAN LIFT MENGGUNAKAN METODE BINARY INTEGER PROGRAMMING - Sofi Ainun Sadikin (2021)
PT. XYZ is a sub contractor company operated in the installation of lift. While company run a project, they often experience problems like material requirements that are not on time. This occur because one of the workstations experienced a delay in the completion of the assembly. Therefore, the overall workload between workstations becomes significantly unbalanced and makes the project delayed. Based on these problems, it is necessary to create a new workstation system that intends to add operators to pursue delays in completion with the approach of line balancing method. But the addition of the operator depends on the value of the penalty delay of each employment contract. The line balancing process is assisted by the binary integer programming method to group the working elements of the precedence diagram. The workstation in actual condition consists of 30 workstations and in the proposed condition consists of 35 workstations. The number of workstations in the proposed conditions can provide greater efficiency and balance than in actual conditions. The line efficiency value is 82.50%, the balance delay is 17.50%, the idle time is 960.34 minutes, and the smoothness index is 224.50 in the proposed condition. Omega Apartment Project has been completed and experienced delays of 14 days. With the proposed system between workstations, delay condition is reduced to 8 days. Although the delay is not reduced to zero day, the proposed system between workstations conditions can be used to anticipate similar events in the future.